The relationship between creativity and global/national identity: Comparative study of Lithuanian and American students’ sample - Tidikis, Viktoria; Donohue, Dana; Petkevičiūtė-Barysienė, Dovilė; Rakickienė, Lauryna (Psichologija, 2018)
The mindset of either a national or global identity was primed in the participants in the United States and Lithuania. The effects of priming on creativity were then examined. Two hundred and eighty-five participants from the United States and 95 Lithuanian participants received one of three possible manipulations: one that primed national identity, one that primed global identity, or no manipulation. They were then asked to complete measures of creativity. The results suggested that participants from Lithuania scored higher than the American participants on measures of national orientation regardless of the condition in which they participated. Lithuanian participants were the most affected by the national prime, and scored particularly low on global orientation when they were in the national identity condition. Lithuanian participants scored higher than participants from the United States on all measures of creativity, regardless of the condition. However, a country-by-condition interaction was also present, showing that participants in the US scored higher on creativity when they were in the global prime condition, while Lithuanians received higher creativity scores when in the national prime condition. Explanations and implications for these results are discussed.